PTU-293 Hes data for ulcerative colitis demonstrates the critical role of the ibd nurse specialist in preventing a&e attendance. (22nd June 2015) - Hayee, B; Dubois, P; Walters, A; Bedwell, T; Tumova, J; Duncan, J; Curtis, H; Irving, P; Forgacs, I
Abstract : Introduction: A key role for an Inflammatory Disease Nurse (IBD) nurse specialist is to act as a first point of contact with secondary care, and as an alternative to the Emergency Department (ED), for a patient with IBD who thinks they may be experiencing a relapse. This opportunistic and observational study allowed the potentially crucial importance of this component of the IBD nurse specialist role to be evaluated. Method: Using hospital episode statistic (HES) data for 2013 (source and acknowledgement….) we analysed the month-by-month variation in ED visits for UC across three NHS Trusts in our region. At Trust 1, a single-handed IBD nurse has been in post since 2002, with a temporary loss of service experienced in April–May 2013, then a planned evaluation of a nurse-led telephone helpline May–Nov 2013 only. At Trust 2, a single-handed IBD nurse was appointed in January 2013 while Trust 3 maintained a stable, hierarchical service with a lead nurse and two junior team members. Comparison of non-linear (cubic) regression curves was with the extra sum of squares F test (GraphPad Prism v4.0). Results: In 2013, there were 144 episodes recorded at Trust 1, 129 at Trust 2 and 90 at Trust 3. The Figure 1 below shows the pattern of ED attendances over the year. Trust 1 recorded zero admissions in Jan-Mar, with a dramatic peak in April coinciding with the loss of service, then settling with the provision of the telephone helpline and rising again with the planned withdrawal of this service (periods shown by shaded bar at top of graph). Trust 2 experienced a gradual decline in attendances (IBD nurse post start denoted by vertical arrow). Trust 3 experienced a stable rate of attendances. A statistically significant difference was observed, and analysing data as a proportion of OP activity or number of medical beds did not affect this analysis. Conclusion: The loss of an IBD nurse specialist is associated with a dramatic rise in ED attendance, while new provision appears to reduce this KPI. Data were not available for 2012, but will be forthcoming for 2014 to determine the durability and magnitude of the trends observed in this study. Disclosure of interest: None Declared.